Chemical Analysis and Comparison of Antitermitic Activity of Essential Oils of Neem (Azadirachta indica), Vetiver (Vetiveria zizanioides) and Mint (Mentha arvensis) against Heterotermes indicola (Wasmann) from Pakistan - Manzoor, Farkhanda; Naz, Narjis; A. Malik, Saadiya; S. Siddiqui, Bina; Syed, Azka; Perwaiz, Sobiya (Asian Journal of Chemistry, 2012)
In present study, three esential oils (neem, vetiver and mint) were analyzed by GC/MS spectroscopy and their physical parameters were also evaluated. The major components of the three oils were: b-terpineol, menthol, isomenthone, menthone, azulene, 5,6-azulenedimethanol, 1H-cycloprop[e]azulene, a-hexylcinnamaldehyde, dihydromyrcenol, ethyl palmitate, methyl(2E,6E)-farnesoate, n-eicosane and n-docosane. The bioactivities of these essential oils were tested for repellency, toxicity and fumigation against the most common termite species of Pakistan, Heterotermes indicola. Results exposed that vetiver oil was the most rerpellent and most toxic killing 60 % termites at concentration of 25 μg/μL while neem and mint oils showed 54 % and 56.66 % mortality rate, respectively at the same concentration. The attribute of vetiver oil as most effective repellent was due to its long lasting activity. For fumigation activity, the three essential oils were tested at concentrations of 0.03125, 0.0625, 0.125, 0.25 and 0.5 %. Out of the three tested oils, vetiver oil was the most valuable fumigent against Heterotermes indicola.